Effects of Si(001) surface amorphization on ErSi2 thin film - Pey, Kin Leong (2013)
In a materials study of ErSi2/Si(001) as a potential candidate for Schottky source/drain NMOS application, the properties of ErSi2 thin film were investigated with varying degrees of Si(001) surface amorphization. The amorphization was carried out by in situ Ar plasma cleaning and Si pre-amorphization implant. It was found that the ErSi2 thin film becomes smoother but less textured and less epitaxial with Si(001) with increasing degree of the Si surface amorphization. In addition, an increased oxygen penetration during rapid thermal annealing occurs with increasing substrate amorphization.